(untitled) (European Journal of Teaching and Education, 2023)
The present study examined the associations between parental conflict and externalising behaviours, specifically in children with Autism Spectrum Disorder (ASD). In addition, parenting styles is explored to moderate the relationship between parental conflict and externalising behaviours in these children with Autism Spectrum Disorder(ASD). Participants comprised of 106 parents of Singaporean children with ASD. Parents were required to complete assessments of autism severity, externalising behaviours, parenting style and interparental conflict. The results from the regression analyses and ANOVA reveal that parenting styles can reduce externalising behaviours in children with ASD, in the context of parental conflict. The findings from the study have implications in designing targeted interventions and parent training programmes to equip parents with appropriate skills to nurture their child, thereby reducing the detrimental outcomes of parental conflict.